Fabrication of Porous Silicon Based Humidity Sensing Elements on Paper. (9th April 2015) - Jalkanen, Tero; Määttänen, Anni; Mäkilä, Ermei; Tuura, Jaani; Kaasalainen, Martti; Lehto, Vesa-Pekka; Ihalainen, Petri; Peltonen, Jouko; Salonen, Jarno
Abstract : A roll-to-roll compatible fabrication process of porous silicon (pSi) based sensing elements for a real-time humidity monitoring is described. The sensing elements, consisting of printed interdigitated silver electrodes and a spray-coated pSi layer, were fabricated on a coated paper substrate by a two-step process. Capacitive and resistive responses of the sensing elements were examined under different concentrations of humidity. More than a three orders of magnitude reproducible decrease in resistance was measured when the relative humidity (RH) was increased from 0% to 90%. A relatively fast recovery without the need of any refreshing methods was observed with a change in RH. Humidity background signal and hysteresis arising from the paper substrate were dependent on the thickness of sensing pSi layer. Hysteresis in most optimal sensing element setup (a thick pSi layer) was still noticeable but not detrimental for the sensing. In addition to electrical characterization of sensing elements, thermal degradation and moisture adsorption properties of the paper substrate were examined in connection to the fabrication process of the silver electrodes and the moisture sensitivity of the paper. The results pave the way towards the development of low-cost humidity sensors which could be utilized, for example, in smart packaging applications or in smart cities to monitor the environment.